First continuous measurements of δ18O-CO2 in air with a Fourier transform infrared spectrometer - Vardag, Sanam Noreen; Hammer, Samuel; Sabasch, Michael; Levin, Ingeborg (Atmospheric measurement techniques discussions, 2015)
The continuous in situ measurement of δ18O in atmospheric CO2 opens a new door to differentiating between CO2 source and sink components with high temporal resolution. Continuous 13C-CO2 measurement systems have already been commercially available for some time, but until now, only few instruments have been able to provide a continuous measurement of the oxygen isotope ratio in CO2. Besides precise 13C/12C observations, the Fourier transform infrared (FTIR) spectrometer is also able to measure the 18O / 16O ratio in CO2, but the precision and accuracy of the measurements have not yet been evaluated. Here we present a first analysis of δ18O-CO2 (and δ13C-CO2) measurements with the FTIR analyser in Heidelberg. We used Allan deviation to determine the repeatability of δ18O-CO2 measurements and found that it decreases from 0.25‰ for 10 min averages to about 0.1‰ after 2 h and remains at that value up to 24 h. We evaluated the measurement precision over a 10-month period (intermediate measurement precision) using daily working gas measurements and found that our spectrometer measured δ18O-CO2 to better than 0.3‰ at a temporal resolution of less than 10 min. The compatibility of our FTIR-spectrometric measurements to isotope-ratio mass-spectrometric (IRMS) measurements was determined by comparing FTIR measurements of cylinder gases and ambient air with IRMS measurements of flask samples, filled with gases of the same cylinders or collected from the same ambient air intake. Two-sample t tests revealed that, at the 0.01 significance level, the FTIR and the IRMS measurements do not differ significantly from each other and are thus compatible. We describe two weekly episodes of ambient air measurements, one in winter and one in summer, and discuss what potential insights and new challenges combined highly resolved CO2, δ13C-CO2 and δ18O-CO2 records may provide in terms of better understanding regional scale continental carbon exchange processes.